2017
DOI: 10.3390/w9120921
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Patterns of the Freshwater Oligochaete Limnodrilus hoffmeisteri Influenced by Environmental Factors in Streams on a Korean Nationwide Scale

Abstract: Aquatic oligochaetes are very common in streams, and are used as biological assessment indicators as well as in the biological management of organic-enriched systems. In this study, we analyzed the effects of environmental factors influencing the distribution of aquatic oligochaetes Limnodrilus hoffmeisteri in streams. We used 13 environmental factors in three categories (i.e., geography, hydrology, and physicochemistry). Data on the distribution of oligochaetes and environmental factors were obtained from 115… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Soonthornvipat et al (2012) reported that oligochaetes constituted an ideal food source for various types of aquaculture fish including ornamental ones. They can survive in highly contaminated sites such as those with high turbidity, in the presence of toxic materials and high levels of organic matter content (Kang et al, 2017). Coldebella et al (2018) recorded that COD, suspended and total solids in addition to the concentrations of some nutrients significantly increased during the time of harvest at aquaculture farms, which released effluents into the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Soonthornvipat et al (2012) reported that oligochaetes constituted an ideal food source for various types of aquaculture fish including ornamental ones. They can survive in highly contaminated sites such as those with high turbidity, in the presence of toxic materials and high levels of organic matter content (Kang et al, 2017). Coldebella et al (2018) recorded that COD, suspended and total solids in addition to the concentrations of some nutrients significantly increased during the time of harvest at aquaculture farms, which released effluents into the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Since the macrobenthic assemblages in polluted reservoirs are normally different from those existing in less polluted reservoirs, at least in terms of their species composition, they have been widely used as bioindicator organisms for assessing water quality changes, especially in reservoir nearshore areas (Kang et al, 2016; Sekiranda et al, 2004). Kang et al (2017) recently reported the aquatic oligochaete tubificid species, L. hoffmeisteri , is distributed throughout South Korea and is widely used as a biological indicator of aquatic pollution. It also is a highly recommended candidate for mitigating organic‐enriched freshwater ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Limnodrilus sp. is a pollution indicator species that can tolerate high nutrient concentrations, low dissolved oxygen concentrations and high pH levels that also are indicators of poor water quality and eutrophication of aquatic systems (Kang et al, 2017;Yap et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The Nakdong River basin (31,785 km 2 ) is in the southeast, and the Geum River basin (17,537 km 2 ) is in the midwest. Lastly, the Yeongsan River (3,467 km 2 ) and Seomjin River (4,912 km 2 ) basins are located close to each other in the southwest of South Korea [4,[22][23][24].…”
Section: Ecological Datamentioning
confidence: 99%